CORPORATE SUSTAINABILITY REPORTING AND INVESTOR SENTIMENT: A SUSTAINABLE DEVELOPMENT PROSPECTIVE ON PAKISTAN-LISTED COMPANIES (Contemporary Journal of Social Science Review, 2025)
This study uses the Pakistan Stock Exchange (PSX) as an example to explore the relationship between environmental, social, and governance (ESG) information disclosure and investor sentiment. ESG disclosure data was obtained from the ESG Sustain platform of the Securities and Exchange Commission of Pakistan (SECP), and an ESG index based on information disclosure was constructed using environmental, social, and governance indicators. Investor sentiment is measured through market-based indicators, particularly stock trading volume and trading activity, which reflect investors’ behavioral responses to ESG-related disclosures. Additionally, company-level control variables, including company size, profitability, leverage ratio, and growth rate, are incorporated. A panel data regression framework is used to assess the impact of ESG information disclosure on investor sentiment. The baseline estimates were performed using a fixed-effects panel regression model to control for unobserved company-specific heterogeneity. Empirical results show a significant correlation between higher ESG disclosure scores and positive investor sentiment. Further analysis shows that the positive impact of environmental and governance information disclosure on investor sentiment is significantly stronger than that of social information disclosure, as evidenced by higher and more statistically significant coefficients estimates Robustness tests and alternative model specifications both confirm these findings. This study contributes to the literature by providing empirical evidence from emerging markets where ESG reporting is still developing. The findings highlight the importance of transparent sustainability reporting for enhancing investor confidence and supporting the development of Pakistan's capital markets.